(untitled) (LACCEI, 2024)
In the present investigation, a system for intelligent irrigation based on the Internet of Things (IoT) was developed, achieving an interconnection of sensors, actuators and software, in addition to this, we worked with 3 study areas, which were the following: "Agronomy ”, the state of the art was carried out on the characterization of the Crimson Giant radish, in this characterization the soil humidity was found to be between 60% and 65% "Computational electronics", where the study was made on microcontrollers, sensors, actuators, and wireless communication, thanks to this a kit was built, which allowed humidity control, activation / deactivation of actuators (pump, solenoid valves) and data sending wirelessly. Finally, "Software", thanks to the scalable system, allowed crop management, configuration and humidity control, and real-time monitoring.